Study on Pressure Relief Zone Formed Inside Roadway Rib by Rotary Cutting with Pressurized Water Jet for Preventing Rock Burst - Zeng-Qiang Yang; Chang Liu; Hui-Wu Jin (Advances in Civil Engineering)
Based on the engineering geological conditions of mining area 2502 in Yanbei coal mine as a background, the comprehensive index method is used to evaluate the rock burst risk of mining area 2502, and the burst tendency of coal seam 5# under natural and water-saturated conditions is also tested in laboratory. Then the pressurized water jet technology is proposed as an effective and feasible method to prevent rock burst. By means of theoretical analysis, the coal-rock mass system has three strain-stress states under the influence of static load, and it has another strain-stress state under the influence of static and dynamic combined load; meanwhile, the greater the horizontal tectonic stress caused by fold structure is, the more prone to instability and failure and induce rock burst coal mass composed of countless cell cubes is; when a pressure relief zone is formed inside the roadway rib by using pressurized water jet technology, the initial single peak stress curve will change to a final bimodal stress curve inside the roadway rib. A “strong-weak-strong” prevention structure can be formed inside the roadway rib and this prevention structure can well prevent the occurrence of rock burst. By means of numerical simulation analysis, the optimal diameter, length, and interval of rotary cutting sections are identified as 400 mm, 3.0 m, and 15.0 m, respectively. By means of on-site industrial application analysis, all these monitoring results verify that when the pressurized water jet is used to conduct rotary cutting of roadway rib, a large-scale pressure relief zone will be formed in the coal mass inside the roadway rib, and it can achieve the purpose of preventing rock burst in the roadway rib. The research results can effectively provide theoretical foundation and a new guidance for preventing rock burst with similar engineering geological conditions.